Interaction With ATM for Blind - Sarfaraz Ahmed; T. Senthil Kumaran (Institute of Advanced Engineering and Science, 2018)
A talking ATM may be a kind of Asynchronous Transfer Mode (ATM) that gives perceptible directions so that persons United Nations agency will not scan associate degree ATM screen can severally use the machine. All perceptible data is delivered in private through an earpiece jack on the face of the device or an on an individual basis hooked up a telephone. Information provided to the client either through pre-recorded sound files or via text-to-speech synthesis A user plugs a conventional telephone receiver into the jack, hear directions and also the user can respond to voice. In spite of everything, the small print is given press OK button for confirmation. There's associate degree perceptible orientation for initial time users, and perceptible data describing the placement of options like the OK button, deposit slot, and card slot. During this application is principally developed for the blind individuals. The blind people cannot see the keyboard and also the screen for the system. They enter the input details through voice. The voice to text converter can convert into text and method additional way. The system offers the instruction regarding the system usage through voice.